Remote ischemic preconditioning does not prevent acute mountain sickness after rapid ascent to 3,450 m - Berger, Marc Moritz; Lehmann, Lukas; Hochreiter, Marcel; Bärtsch, Peter; Mairbäurl, Heimo (Journal of applied physiology, 2017)
Remote ischemic preconditioning (RIPC) has been shown to protect remote organs, such as the brain and the lung, from damage induced by subsequent hypoxia or ischemia. Acute mountain sickness (AMS) is a syndrome of nonspecific neurologic symptoms and in high-altitude pulmonary edema excessive hypoxic pulmonary vasoconstriction (HPV) plays a pivotal role. We hypothesized that RIPC protects the brain from AMS and attenuates the magnitude of HPV after rapid ascent to 3,450 m. Forty nonacclimatized volunteers were randomized into two groups. At low altitude (750 m) the RIPC group (n = 20) underwent 4 × 5 min of lower-limb ischemia (induced by inflation of bilateral thigh cuffs to 200 mmHg) followed by 5 min of reperfusion. The control group (n = 20) underwent a sham protocol (4 × 5 min of bilateral thigh cuff inflation to 20 mmHg). Thereafter, participants ascended to 3,450 m by train over 2 h and stayed there for 48 h. AMS was evaluated by the Lake Louise score (LLS) and the AMS-C score. Systolic pulmonary artery pressure (SPAP) was assessed by transthoracic Doppler echocardiography. RIPC had no effect on the overall incidence (RIPC: 35%, control: 35%, P = 1.0) and severity (RIPC vs. control: P = 0.496 for LLS; P = 0.320 for AMS-C score) of AMS. RIPC also had no significant effect on SPAP [maximum after 10 h at high altitude; RIPC: 33 (SD 8) mmHg; controls: 37 (SD 7) mmHg; P = 0.19]. This study indicates that RIPC, performed immediately before passive ascent to 3,450 m, does not attenuate AMS and the magnitude of high-altitude pulmonary hypertension.NEW & NOTEWORTHY Remote ischemic preconditioning (RIPC) has been reported to improve neurologic and pulmonary outcome following an acute ischemic or hypoxic insult, yet the effect of RIPC for protecting from high-altitude diseases remains to be determined. The present study shows that RIPC, performed immediately before passive ascent to 3,450 m, does not attenuate acute mountain sickness and the degree of high-altitude pulmonary hypertension. Therefore, RIPC cannot be recommended for prevention of high-altitude diseases.
Gesehen am 27.04.2018